Hypercholesterolemia Induces a Mast Cell-CD4 + T Cell Interaction in Atherosclerosis - Kritikou, Eva; van der Heijden, Thomas; Swart, Maarten; van Duijn, Janine; Slütter, Bram; Wezel, Anouk; Smeets, Harm J; Maffia, Pasquale; Kuiper, Johan; Bot, Ilze (The Journal of immunology (1950), 2019)
Mast cells (MCs) are potent innate immune cells that aggravate atherosclerosis through the release of proinflammatory mediators inside atherosclerotic plaques. Similarly, CD4 T cells are constituents of the adaptive immune response and accumulate within the plaques following lipid-specific activation by APCs. Recently it has been proposed that these two cell types can interact in a direct manner. However, no indication of such an interaction has been investigated in the context of atherosclerosis. In our study, we aimed to examine whether MCs can act as APCs in atherosclerosis, thereby modulating CD4 T cell responses. We observed that MCs increased their MHC class II expression under hyperlipidemic conditions both in vivo and in vitro. Furthermore, we showed that MCs can present Ags in vivo via MHC class II molecules. Serum from high-fat diet-fed mice also enhanced the expression of the costimulatory molecule CD86 on cultured MCs, whereas OVA peptide-loaded MCs increased OT-II CD4 T cell proliferation in vitro. The aortic CD4 and T cell content of atherosclerotic mice that lack MCs was reduced as compared with their wild-type counterparts. Importantly, we identified MCs that express HLA-DR in advanced human atheromata, indicating that these cells are capable of Ag presentation within human atherosclerotic plaques. Therefore, in this artice, we show that MCs may directly modulate adaptive immunity by acting as APCs in atherosclerosis.